1981
DOI: 10.1111/j.1432-1033.1981.tb06421.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fatty Acid Composition of Subcellular Membranes of Rat Liver, Heart, and Brain : Diet‐Induced Modifications

Abstract: The influence of diets having different fatty acids composition on the fatty acid content of (the phospholipids) of rat liver mitochondria and microsomes, heart mitochondria, brain mitochondria and microsonies has been analyzed. It has been found that each organelle has its own peculiar composition in fatty acids. This composition may be profoundly influenced by the diet, but to different degrees in different organelles. Those of brain are most resistant. The changes observed are rather rapid, being generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
35
0
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(49 citation statements)
references
References 29 publications
13
35
0
1
Order By: Relevance
“…branes have also been reported [39,79,134,140]. In general, the developing brains of young animals can be modulated with dietary FAs supplemented over a short period of just a few weeks, as has been reported in mice [74], guinea pigs [155], and chicks [3].…”
Section: The Eects Of Dietary Fats On Brain Fatty Acid Compositionmentioning
confidence: 71%
“…branes have also been reported [39,79,134,140]. In general, the developing brains of young animals can be modulated with dietary FAs supplemented over a short period of just a few weeks, as has been reported in mice [74], guinea pigs [155], and chicks [3].…”
Section: The Eects Of Dietary Fats On Brain Fatty Acid Compositionmentioning
confidence: 71%
“…Moreover, the addition of spermine in RBM slightly increases the DW value with respect to the control condition. This observation may be explained by recalling that RBM and RLM have significantly different compositions in the fatty acid contents of membrane phospholipids (Tahin et al 1981). This fact most probably accounts for the physiologically higher proton permeability of RBM membranes, when compared with RLM, which would be responsible for the low DW value of RBM.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary 22:6n-3 has been associated with decreased 20:4n-6 in various tissues (19)(20)(21)(22)(23)(24)(25)(26), and dietary 22:6n-3 is considered to compete directly with 20:4n-6. It has been suggested that feeding 22:5n-6 along with 22:6n-3 may maintain 20:4n-6 levels in tissues via 22:5n-6 retroconversion (19).…”
Section: Discussionmentioning
confidence: 99%